The Relationship of Fashion Involvement with Impulse Buying through Online Shop for Students - Aflaha, Nadia Nufida; Matulessy, Andik; Rini, Rr. Amanda Pasca (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the activities that students often do by taking advantage of advanced technology is shopping. Students have a sensitivity to what is trendy and tend to follow the latest fashion trends. This research aims to determine the relationship between fashion involvement and impulse buying through online shops among students. This research uses quantitative research. The subjects in this research were 350 people. The sampling technique uses simple random sampling technique. The data collection method used in this research is a Likert scale. The fashion involvement measuring tool used in this research uses a scale from the aspects expressed by Peter and Olson (2013). Meanwhile, the impulse buying measuring tool uses a scale from the aspects expressed by Verplanken and Herabadi (2001). The results of this research show that there is a significant relationship between fashion involvement and impulse buying through online shops among students with a Pearson correlation value of 0.432 and p = 0.000 (p<0.05). These results show that the higher the fashion involvement, the higher the impulse buying through online shops among students.